P68-S The effect of compression on peripheral nerves in ALS patients. Issue 7 (July 2019) - Sirin, Gorkem; Gunes, Taskin; Isak, Baris
Abstract : Background: Compression over a peripheral nerve leads to several changes in structural and physiological properties of that nerve. Paranodal myelin abnormalities and impaired axonal transport are some pathological incidents defined after acute compression. Materials and methods: In sixteen ALS patients and 16 controls, CMAP Scan curves were recorded from first dorsal interosseus (FDI) muscle by stimulating ulnar nerve at elbow before compression, compression in 5 consecutive CMAP scanning cycles, and after compression. Stimulus intensities needed to elicit 10% and 90% of CMAP and step number and step% were calculated for each scan. As a further comparison, areas under CMAP scan curves were examined using natural values, percentages, and differences between compression (comp) cycles. Results: For both patients and controls, conventional CMAP scan parameters were not significantly different in consecutive cycles. During compression, a tendency of reduction in area under CMAP scan curve of ALS patients (164.8 mVms, 156.3 mVms, 146.5 mVms, 142.1 mVms, 142.7 mVms, 137 mVms, and 174.9 mVms for pre-comp, 1st comp, 2nd comp, 3rd comp, 4th comp, 5th comp, and post- comp cycles, respectively) and a tendency of increase in CMAP scan curve area of healthy subjects (283.3 mVms, 315.6 mVms, 298.5 mVms, 319.7 mVms, 336.1 mVms, 361.4 and 308.1 mVms for pre-comp, 1st comp, 2nd comp, 3rd comp, 4th comp, 5th comp, and post- comp cycles, respectively) were observed. Conclusions: Probably due to incidental changes in nerve excitability, ALS patients mostly reacted differently to nerve compression when compared with healthy subjects.